Synthesis of Styrofoam Waste-Derived Activated Carbon as an Electron Extractor for Modifying Cu/P-CuSCN/N-Cu₂O/ITO Photovoltaic Cells - Dheani Laily; Aisyah Wahyu Fitriani; Endar Aldi Hanantya; Rahmad Nuryanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Activated carbon synthesized from styrofoam waste was applied as an electron extractor to enhance the performance of Cu/p-CuSCN/n-Cu2O/ITO-based photovoltaic cells. The widespread use of plastic products, particularly styrofoam, has led to severe environmental pollution due to its long decomposition time. Styrofoam waste-derived activated carbon utilizes polystyrene, which is rich in carbon, to produce high-surface-area materials. In this study, the activated carbon enhances the efficiency of photogenerated electron separation and extraction in photovoltaic cells. Characterization results indicate that the activated carbon has a surface area of 1,865.04 m2/g, a pore volume of 1.25 cm3/g, and a pore diameter of 2.53–2.68 nm, with a direct band gap energy of 4.33 eV. Voltage testing on the photovoltaic cells demonstrated a significant increase, with the highest voltage reaching 209.67 mV in the 5 mg activated carbon variation, representing a 34.84% improvement. The application of activated carbon in Cu/p-CuSCN/n-Cu2O/ITO-based photovoltaic cells provided a notable voltage increase, confirming its effectiveness as an electron extractor.